2022
DOI: 10.3390/foods11203190
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Genomic Characterization of the First Reported optrA-Carrying Linezolid-Resistant Enterococci Isolated from Retail Broiler Meat in the United Arab Emirates

Abstract: The foodborne transfer of resistant genes from enterococci to humans and their tolerance to several commonly used antimicrobials are of growing concern worldwide. Linezolid is a last-line drug for managing complicated illnesses resulting from multidrug-resistant Gram-positive bacteria. The optrA gene has been reported in enterococci as one of the acquired linezolid resistance mechanisms. The present study uses whole-genome sequencing analysis to characterize the first reported isolates of linezolid-resistant E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…among livestock across different geographic regions can be attributed to differences in dietary patterns, which impact the composition of gut commensal bacteria ( Klibi et al, 2013 ; Ngbede et al, 2017 ). Similar to our findings, other studies ( Golob et al, 2019 ; Habib et al, 2022 ) have also reported consistent contamination of retail meat by Enterococcus spp. and this has been linked to fecal contamination.…”
Section: Discussionsupporting
confidence: 93%
“…among livestock across different geographic regions can be attributed to differences in dietary patterns, which impact the composition of gut commensal bacteria ( Klibi et al, 2013 ; Ngbede et al, 2017 ). Similar to our findings, other studies ( Golob et al, 2019 ; Habib et al, 2022 ) have also reported consistent contamination of retail meat by Enterococcus spp. and this has been linked to fecal contamination.…”
Section: Discussionsupporting
confidence: 93%
“…Linezolid, the first clinically available oxazolidinone, is globally used in human medicine as a last-resort antimicrobial agent to treat infections caused by multidrug-resistant Gram-positive pathogens, such as VRE [ 107 , 108 ]. This drug class is not approved for food animals in the USA and EU and, as expected, Tyson et al (2018) reported very low levels of linezolid-resistant Enterococcus spp.…”
Section: Enterococcus Sppmentioning
confidence: 99%
“…(LRE) from food animal cecal content in the USA, and De Jong et al (2019) revealed that commensal enterococci from healthy cattle, pigs, and chickens across Europe and broiler breeder farms in Korea were rarely resistant to linezolid [ 69 , 93 , 109 ]. In the United Arab Emirates, Habib et al (2022) reported as well low levels of LRE from retail broiler meat [ 107 ]. Besides linezolid, daptomycin, which is a cyclic lipopeptide antibiotic, is also used for the treatment of complicated infections caused by Gram-positive organisms.…”
Section: Enterococcus Sppmentioning
confidence: 99%
See 2 more Smart Citations